Mechanical behaviour and formation process of silkworm silk gut. Issue 46 (25th September 2015) - Cenis, José L.; Madurga, Rodrigo; Aznar-Cervantes, Salvador D.; Lozano-Pérez, A. Abel; Marí-Buyé, Núria; Meseguer-Olmo, Luis; Plaza, Gustavo R.; Guinea, Gustavo V.; Elices, Manuel; Del Pozo, Francisco; Pérez-Rigueiro, José
Abstract : Silkworm silk gut shows intrinsic properties comparable to those of natural silkworm silk, but obtained with an alternative spinning procedure. Abstract : High performance silk fibers were produced directly from the silk glands of silkworms ( Bombyx mori ) following an alternative route to natural spinning. This route is based on a traditional procedure that consists of soaking the silk glands in a vinegar solution and stretching them by hand leading to the so called silkworm guts. Here we present, to the authors' best knowledge, the first comprehensive study on the formation, properties and microstructure of silkworm gut fibers. Comparison of the tensile properties and microstructural organization of the silkworm guts with those of naturally spun fibers allows gain of a deeper insight into the mechanisms that lead to the formation of the fiber, as well as the relationship between the microstructure and properties of these materials. In this regard, it is proved that an acidic environment and subsequent application of tensile stress in the range of 1000 kPa are sufficient conditions for the formation of a silk fiber.